Nutrition support in critically ill COVID-19 patients - Abdolreza Norouzy (World Nutrition Journal, 2020)
Diagnosis and treatment of malnutrition should be considered in the management of COVID-19 patients to improve both short- and long-term prognosis. Patients at risk for poor outcomes and higher mortality following infection with COVID-19, namely older adults and polymorbid individuals, should be checked for malnutrition through screening and assessment.